Legal Protection for Women as Victims of Online Gender-Based Violence Through Deepfake Pornography Using Artificial Intelligence (AI) - Annisa Rachmasari; Nurwati; J. Jopie Gilalo (DE'RECHTSSTAAT, 2026)
The rapid development of technology in the era of the Industrial Revolution 4.0 has led to the emergence of Artificial Intelligence (AI), which offers various benefits in facilitating human activities. However, the misuse of AI technology has also created new legal challenges, particularly in the form of cybercrime. One emerging form of cybercrime is the use of deepfake technology to manipulate voices, faces, and personal data for pornographic purposes. This phenomenon has significantly contributed to the rise of online gender-based violence (GBV), in which women constitute the majority of victims. Such crimes pose serious challenges for governments and law enforcement agencies in providing adequate legal protection for victims. Considering that law must be dynamic and responsive to technological developments, it is necessary to strengthen legal frameworks addressing these issues. This study employs a normative juridical method using a statutory approach by examining relevant laws and regulations related to the legal issues under study. The findings indicate that the government is obliged to provide preventive legal protection through public education and the formulation of specific regulations governing Artificial Intelligence more comprehensively. In addition, repressive legal protection must be ensured through effective law enforcement, victim-oriented judicial processes, and strict punishment for perpetrators. Furthermore, victims should receive adequate rehabilitation and restitution due to the psychological, emotional, and social harms caused by such crimes.